MTOR inhibitors improve both humoral and cellular response to SARS‐CoV‐2 messenger RNA BNT16b2 vaccine in kidney transplant recipients. Issue 5 (28th January 2022) - Netti, Giuseppe S.; Infante, Barbara; Troise, Dario; Mercuri, Silvia; Panico, Maddalena; Spadaccino, Federica; Catalano, Valeria; Gigante, Margherita; Simone, Simona; Pontrelli, Paola; Gesualdo, Loreto; Ranieri, Elena; et al.
Abstract : Kidney transplant recipients (KTRs) have been considered as patients at higher risk of SARS‐CoV‐2‐related disease severity, thus COVID‐19 vaccination was highly recommended. However, possible interferences of different immunosuppression with development of both humoral and T cell–mediated immune response to COVID‐19 vaccination have not been determined. Here we evaluated the association between mTOR‐inhibitors (mTOR‐I) and immune response to mRNA BNT162b2 (Pfizer‐BioNTech) vaccine in KTR. To this aim 132 consecutive KTR vaccinated against COVID‐19 in the early 2021 were enrolled, and humoral and T cell–mediated immune response were assessed after 4–5 weeks. Patients treated with mTOR‐I showed significantly higher anti‐SARS‐CoV‐2 IgG titer ( p  = .003) and higher percentages of anti‐SARS‐CoV‐2 S1/RBD Ig ( p  = .024), than those without. Moreover, SARS‐CoV‐2‐specific T cell–derived IFNγ release was significantly increased in patients treated with mTOR‐I ( p  < .001), than in those without. Multivariate analysis confirmed that therapy with mTOR‐I gained better humoral ( p  = .005) and T cell–mediated immune response ( p  = .005) in KTR. The presence of mTOR‐I is associated with a better immune response to COVID‐19 vaccine in KTR compared to therapy without mTOR‐I, not only by increasing vaccine‐induced antibodies but also by stimulating anti‐SARS‐CoV‐2 T cell response. These finding are consistent with a potential beneficial role of mTOR‐I as modulators of immune response to COVID‐19 vaccine in KTR. Abstract : In kidney transplant recipients, mTOR inhibitors compared with calcineurin inhibitors is associated with higher levels of COVID‐19 vaccine‐induced antibodies and stronger anti‐SARS‐CoV‐2 T‐cell response.